2022
DOI: 10.2147/idr.s360238
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implication of the Effect of the Production of Neutralizing Antibodies Against SARS-Cov-2 for Chronic Immune Thrombocytopenia Flare-Up Associated with COVID-19 Infection: A Case Report and the Review of Literature

Abstract: Previous studies have demonstrated that the appropriate production of serum anti-severe acute respiratory syndrome coronavirus 2 (SARS-Cov-2) neutralizing antibody (nAb) plays a critical role in the recovery from coronavirus disease 2019 (COVID-19); however, the role of nAb production in the recovery from a flare-up of chronic immune thrombocytopenia (ITP) has been unknown. We here report the first retrospectively investigated case of serum anti-SARS-Cov-2 nAb production during chronic ITP flare-up triggered b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The phenomenon of thrombocytosis following COVID-19 infection in ITP patients receiving TPO-RA therapy has been described in a few cases before (Table 1 ) [ 5 , 9 , 11 ]. Similar to our case, Pantic et al reported severe thromboembolic complications in their patient cohort associated with post-COVID-19 thrombocytosis approximately seven days after COVID-19 onset.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The phenomenon of thrombocytosis following COVID-19 infection in ITP patients receiving TPO-RA therapy has been described in a few cases before (Table 1 ) [ 5 , 9 , 11 ]. Similar to our case, Pantic et al reported severe thromboembolic complications in their patient cohort associated with post-COVID-19 thrombocytosis approximately seven days after COVID-19 onset.…”
Section: Discussionmentioning
confidence: 99%
“…A reduced number of auto-reactive lymphocytes may lead to inhibition of ITP-related platelet destruction, and TPO-RA may promote reactive thrombocytosis due to ongoing stimulation of thrombopoiesis [ 5 ]. Maekura et al [ 9 ] suggested an association between elevated platelets in chronic ITP patients and the development of SARS-CoV-2 neutralizing antibodies after a COVID-19 infection. Four out of 13 cases, including our case, revealed severe thromboembolic complications during elevated platelet counts after COVID-19 infection in ITP patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation